Accumulation of p27(kip1) is associated with cyclin D3 overexpression in the oxyphilic (Hurthle cell) variant of follicular thyroid carcinoma. Issue 4 (23rd June 2006) - Troncone, G; Iaccarino, A; Russo, M; Palmieri, E A; Volante, M; Papotti, M; Viglietto, G; Palombini, L
Abstract : Background: The down regulation of protein p27 kip1 (p27) in most cases of thyroid cancer has relevant diagnostic and prognostic implications. However, the oxyphilic (Hurthle cell) variant of follicular thyroid carcinoma expresses more p27 than benign oxyphilic lesions do. Aim: To evaluate the mechanism underlying this difference in expression of p27. Methods: Because high levels of cyclin D3 lead to p27 accumulation in cell lines and clinical samples of thyroid cancer, the immunocytochemical pattern of cyclin D3 in oxyphilic (n = 47) and non-oxyphilic (n = 70) thyroid neoplasms was investigated. Results: In the whole study sample, there was a significant correlation between p27 and cyclin D3 expression (Spearman's r: 0.64; p<0.001). The expression of cyclin D3 and p27 was significantly higher in the oxyphilic variant of follicular carcinomas than in non-oxyphilic carcinomas (p<0.001). In the former, cyclin D3 overexpression and p27 accumulation were observed in a median of 75% and 55% of cells, respectively. In co-immunoprecipitation experiments, the level of p27-bound cyclin D3 was much higher in oxyphilic neoplasias than in normal thyroids and other thyroid tumours. Conclusion: These results show that increased p27 expression in the oxyphilic (Hurthle cell) variant of follicular thyroid carcinoma results from cyclin D3 overexpression.